Misoprostol for medical treatment of missed abortion: a systematic review and network meta-analysis - Hang-lin Wu (Nature Portfolio, 2017)
Abstract The efficacy and safety of misoprostol alone for missed abortion varied with different regimens. To evaluate existing evidence for the medical management of missed abortion using misoprostol, we undertook a comprehensive review and meta-analysis. The electronic literature search was conducted using PubMed, the Cochrane Library, Embase, EBSCOhost Online Research Databases, Springer Link, ScienceDirect, Web of Science, Ovid Medline and Google Scholar. 18 studies of 1802 participants were included in our analysis. Compared with vaginal misoprostol of 800 ug or sublingual misoprostol of 600 ug, lower-dose regimens (200 ug or 400 ug) by any route of administration tend to be significantly less effective in producing abortion within about 24 hours. In terms of efficacy, the most effective treatment was sublingual misoprostol of 600 ug and the least effective was oral misoprostol of 400 ug. In terms of tolerability, vaginal misoprostol of 400 ug was reported with fewer side effects and sublingual misoprostol of 600 ug was reported with more side effects. Misoprostol is a non-invasive, effective medical method for completion of abortion in missed abortion. Sublingual misoprostol of 600 ug or vaginal misoprostol of 800 ug may be a good choice for the first dose. The ideal dose and medication interval of misoprostol however needs to be further researched.